AL-FĀTIḤAH AS A PARADIGM OF INTERPRETATION - Wardani Wardani (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2021)
Thought on the methodology of interpreting the Qur'an in Indonesia cannot be separated from several contemporary Muslim scholars. Some of them gave a new explanation that developed from the treasures of classical concepts. This paper discusses the thoughts of M. Dawam Rahardjo, one of the contemporary Muslim scholars, on al-Fātiḥah as a paradigm of interpretation of the Qur'an. This surah, based on the explanation of the Prophet Muhammad, is only referred to as "the mother of the Qur'ān” (umm al-Qur`ān) because it summarizes the central teachings of the Qur'an. However, the Prophet's explanation was not explored in more depth, so that it was only believed to have no methodological implications in the interpretation of the Qur'an. Using the historical-philosophical approach, the author will examine Dawam's thoughts from the perspective of originality, in terms of continuity-change and epistemology, in terms of the rationality of thought. This paper concludes that, firstly, this idea, although initially based on the Prophet's statement, is further developed by saying that al-Fātiḥah is a surah whose verses are muhkam and whose content is universal. So that in interpretation, it must be referred to as a paradigm when interpreting verses in other surahs which explain the details. Second, in the context of the study of thought, by its nature, Dawam's thought tends to be monolithic-rationalism. Although he draws this thought from traditional sources (nash, hadīts), this method of interpretation has a rational character and makes these traditional sources the primary source, which he developed. Keyword: al-Fātiḥah, paradigm, the mother of the Qur`an, muḥkam, mutasyābih